Listeria monocytogenes endophthalmitis – case report with a good visual outcome - Grad, Milena; Duda, Patrycja; Terelak-Borys, Barbara; Czapczyńska, Edyta; Grabska-Liberek, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
Endogenic endophthalmitis due to Listeria monocytogenes infection is an uncommon entity, affecting mainly immunocompromised patients. This case report addresses infectious endophthalmitis caused by this pathogen in a patient with plasmacytic myeloma. The condition manifested primarily as acute anterior uveitis. Microbiological analysis of an anterior chamber fluid sample confirmed the presence of L. monocytogenes, while blood and vitreous body cultures were negative. A combination therapy involving high-dose systemic ampicillin treatment and intravitreal injections of vancomycin resulted in full recovery and restoration of visual acuity.